Kajian bisnis alat tangkap bagan apung di Perairan Pulau Katela Kabupaten Muna Barat - Ramadhan, Dafis; La Ola, La Onu; Mansyur, Akhmad; Ruslaini; Yusuf, Sarini; Sriwulan, Desy (Universitas Halu Oleo, 2022)
This research aims to examine the production cost and profits in the floating fish trap fisheries Katela Village Tiworo Islands West Muna Regency, South East Sulawesi. This research was conducted in January 2021. Location was determined intentionally (purposive) using a simple random sample technique method so that 45 of 85 floating fish trap fishermen were selected as respondents. Primary data was obtained from floating fish trap fishermen by means of observation and interviews directly using structured questionnaires. Primary data collected include age, education, business experience, fishing costs, amount of production and market price, whereas secondary data obtained from the Central Statistics Agency of Tiworo Islands sub district that consists of population, geographical location, territorial boundaries, climate conditions and other data related to this study. The data obtained was calculated using the formula of total cost, cost of production, and profit. The results of the analysis showed that the cost of production in the floating fish trap fisheries was the lowest of IDR5,440/kg, and the highest up to IDR10,216/kg. Profits in the floating fish trap fisheries were the lowest at IDR3,145,836/month, and the highest at IDR4,729,329/month, with an average of IDR3,967,405/month. Therefore, the fishermen of floating fish trap in Katela village is categorized as having very high income thus it is very important to maintain the fisheries in order to create a better fishermen welfare.